Assessing the capacity of local ecosystems to meet industrial demand for ecosystem services. Issue 9 (5th July 2016) - Gopalakrishnan, Varsha; Bakshi, Bhavik R.; Ziv, Guy
Abstract : Despite the importance of ecosystems, engineering activities continue to ignore or greatly undervalue their role. Consequently, engineered systems often overshoot nature's capacity to support them, causing ecological degradation. Such systems tend to be inherently unsustainable, and they often fail to benefit from nature's ability to provide essential goods and services. This work explores the idea of including ecosystems in chemical processes, and assesses whether such a techno‐ecological synergistic system can operate within ecological constraints. The demand for ecosystem services is quantified by emissions and resources used, while the supply is provided by ecosystems on the manufacturing site. Application to a biodiesel manufacturing site demonstrates that ecosystems can be economically and environmentally superior to conventional technologies for making progress toward zero emissions and net positive impact manufacturing. These results highlight the need for shifting the paradigm of engineering from that of dominating nature to embracing nature and respecting its limits. © 2016 American Institute of Chemical Engineers AIChE J, 62: 3319–3333, 2016